Hybrid education, an approach of STE(A)M, hybrid learning and hybrid labs2 - Mertik, Matej (Monitor ISH, 2022)
STEAM education is an approach that integrates Science, Technology, Engineering, Arts, and Mathematics to create a holistic learning experience. It prepares students for the 21st century needs, develops skills for success in any field and incorporates hands-on learning through projects, experiments, and interactive activities including problem-solving, creative thinking, collaboration, teamwork, and innovation. The HYBRID lab network project, which was an ERASMUS+ project, developed an upgraded STEAM methodology with integrated principles including the fields of humanities for educating students through experiences and practices. This paper presents the methodology, practices and benefits of Hybrid learning in order to expose these perspectives to a broader audience in the sense of educating people for the future.
Keywords: education; hibridni laboratorij; hibridno učenje; hybrid laboratory; hybrid learning; interdisciplinarity; interdisciplinarnost; izobraževanje; Vzgoja in izobraževanje